2010
DOI: 10.1007/s13337-011-0023-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Phylogeny of a Phytoplasma Associated with Phyllody Disease of toria (Brassica rapa L. subsp. dichotoma (Roxb.)) in India

Abstract: Samples from toria plants (Brassica rapa L. subsp. dichotoma (Roxb.)) exhibiting phyllody, virescence, witches broom, extensive malformation of floral parts, formation of bladder like siliquae and flower sterility were collected from four different locations in India. Sequencing and phylogenetic analysis of the 16S rRNA, a part of 23S rRNA, partial sec A genes, rp gene and 16S-23S intergenic spacer region indicated that the phytoplasmas associated with toria phyllody (TP) symptoms were identical and belonged t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…toria), and yellow sarson (B. rapa var. yellow sarson) in the states of Punjab, Haryana, New Delhi, and Uttar Pradesh (Kolte 1985, Azadvar andBaranwal 2010) in India. In Canada, aster yellows (AY) has also been reported on B. napus and B. rapa (Olivier et al 2010).…”
Section: Geographical Distribution and Lossesmentioning
confidence: 99%
See 3 more Smart Citations
“…toria), and yellow sarson (B. rapa var. yellow sarson) in the states of Punjab, Haryana, New Delhi, and Uttar Pradesh (Kolte 1985, Azadvar andBaranwal 2010) in India. In Canada, aster yellows (AY) has also been reported on B. napus and B. rapa (Olivier et al 2010).…”
Section: Geographical Distribution and Lossesmentioning
confidence: 99%
“…The phyllody disease is reported to be caused by the Candidatus Phytoplasma asteris (Phytoplasma asteris) phytoplasma of subgroup 16Srl-A, 16Srl-B, and 16SrlX-C , Maliogka et al 2009, Azadvar and Baranwal 2010, Rampin et al 2010, Zwolinska et al 2011. The AY disease is reported to be caused by the phytoplasma of 16Srl-A and 16Srl-B subgroup (Olivier et al 2010).…”
Section: Pathogenmentioning
confidence: 99%
See 2 more Smart Citations
“…Result similar to the present investigation has already proposed by Win et al (2011) indicated that China aster as a new host for a subgroup 16SrII-A phytoplasma. The 16S rDNA gene has not been sequenced completely for most of the phytoplasmas (Azadvar and Baranwal, 2010). Whether rDNA gene, encoding 16S can be used for finer differentiation of phytoplasmas in a group or not will be known when more sequences of phytoplasma in a group become available.…”
Section: Resultsmentioning
confidence: 99%